MODELING POPULATION GROWTH RATE IN RUSSIAN CITIES: SPATIAL ASPECTS - Olga S. Balash (Статистика и экономика)
The article analyzes the growth rate of the urban population in Russia according to their size and region. It is revealed that the growth rate of the urban population are not the same for the regions of Russia. An econometric analysis of the data with geo-referenced using geographically weighted regression is conducted. In order to determine the causes of urban growth rate geographic market potential offered by Soo is used.